1995
DOI: 10.1288/00005537-199503000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Inverted papilloma: A report of 112 cases

Abstract: Inverted papilloma is a benign sinonasal tumor which is locally aggressive and has a significant malignant potential. This report updates the experience of the two senior authors, who have treated 112 patients with inverted papilloma at the Mount Sinai Medical Center over a 20-year period. As clinical examination often underestimates tumor extent, preoperative radiographic assessment is of paramount importance in guiding selection of surgical therapy. Complete en bloc excision via lateral rhinotomy and medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
269
0
24

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(307 citation statements)
references
References 41 publications
13
269
0
24
Order By: Relevance
“…Inverted papilloma is known to have a peak incidence in patients during their fth to seventh decades, [1][2][3]12 and our results support these reports. There were no patients under the age of 30 and especially no patients of paediatric age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Inverted papilloma is known to have a peak incidence in patients during their fth to seventh decades, [1][2][3]12 and our results support these reports. There were no patients under the age of 30 and especially no patients of paediatric age.…”
Section: Discussionsupporting
confidence: 90%
“…As other authors have repeatedly shown, 1,5,7,12,13 our series indicates that aggressive surgical procedure can reduce the recurrence rate of inverted papilloma. Our conservative-treatment group showed a somewhat higher recurrence rate (33.9 per cent) when compared with other reported conservative-treatment groups (around 18 per cent).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Inverted papillomas (IP) are two to five times more common in males and are found primarily in the 40 -70-year age group (2,3,8,14,15,(23)(24)(25)(26)(27)(28)(29)(30). The 6-year-old boy included in the series of Eavey (31) is one of the youngest patients yet described with this papilloma.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Sinonasal IP comprises 0.5-4% of all nasal cavity and paranasal tumors, and accounts for approximately 10% of all squamous cell carcinoma (SCC) cases [1,2]. About 40% of patients with SCC-ex-IP will die of the disease within 3 years [3], yet its etiology is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%